(untitled)
We examine the strategic interaction in the market for physician services when the total budget for reimbursement is fixed. We show that this prospective payment system involves compared to a fee-for-service remuneration system a severe coordination problem, which potentially leads to the treadmill effect. For the institutional setting of German primary physician service we provide evidence for decreasing reimbursement per treatment, which is consistent with theoretical predictions. When market entry is possible, a budget can be efficiency enhancing, if in addition a price floor is used., address = Munich, author = Franz Benstetter and Achim Wambach, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, keywords = 330; Health economics; supplier-induced demand; remuneration systems; coodination device, language = eng, number = 427, publisher = Center for Economic Studies and ifo Institute (CESifo), title = Strategic Interaction in the Market for Physician Services: The Treadmill Effect in a Fixed Budget System, type = CESifo Working Paper, url = https://hdl.handle.net/10419/75858, year = 2001